Theoretical Bases and Peculiarities of Children's Literature as a Subject of Research - Nosirova Gulnora (International Journal on Integrated Education, 2022)
The article deals with the issues based on theoretical bases and peculiarities of children's literature as a subject of research. It is known that children's literature belongs to the realm of the art of the word. This determines its aesthetic function. It is associated with a special kind of emotions that arise when reading literary works. Children are able to experience aesthetic pleasure from reading as adults, they can happily dive into the fantasy world of fairy tales and adventures, empathizes with fictional characters, rejoices in poetic rhythm, sound and word play, as well as, they understand humor and jokes well. The role of an adult is enormous, who is able to play the role of a guide in comprehending child of the treasures of world and national literature. At the same time, the reverse process is also important: by reading children's literature, adults begin to better understand children, their problems and interests.